ENTITLING TELEVISION PROGRAMS USING ENGLISH LOANWORDS IN SOME INDONESIAN TV STATIONS - Abdulloh Abdulloh; Sarsono Sarsono; Ikhwan Muslim; Slamet Basuki (STIBA IEC JAKARTA, 2023)
Loan words or borrowing words have already dominated in almost all of our everyday lives. All aspects of lives have already been inserted by foreign languages due to increasing the frequency of our contact with other nations through language. One of the examples is English loanwords in entitling the TV program in some Indonesian TV stations. This paper investigates the English words, phrases, expressions borrowed by Indonesian to entitle TV programs in 5 TV stations. Besides investigating the borrowing words, the writer also investigates the word class and borrowing process classification . The result of the research ranges 40% – 94.12 % of those 5 TV stations used English loanwords or phrases in entitling the program. The dominant process of loanwords still adoption, it ranges 33,310% - 100%, the second rank is adaptation , it ranges 9.5% -27.8 %, and the last one is one the three process of loanword, adoption, adaptation, and translation mixed with Indonesian. It ranges from 9.5 % to 38.9 %. Translation and creation are not clearly detected. In conclusion, almost all National TV stations are unavoidable using English loanwords in entitling the programs even TVRI as official TV station of this country. significantly influenced by them